UJI POTENSI MINYAK ATSIRI DAUN JERUK PURUT (Citrus Hystrix D.C) SEBAGAI ANTIOKSIDAN DAN ANTIBAKTERI - Dwi Rizki Febrianti; Novia Ariani (Jurnal Insan Farmasi Indonesia, 2020)
The identified major compounds from Kaffir lime peels oil were sabinene, ÃŸ-pinene, limonene, a-pinene, There has a good potential for antioxidant and antimicrobial This is important because more than 50% antimicrobial drugs discovered a few decades of natural product. the number pathogens that are resistant to commercial drugs has increased. kaffir lime is one of the compounds from natural sources to be expected to have great anti-microbial activities. kaffir lime leaves (720 g) were collected from the plantation to hydrodistillation for 7 hours to obtain the essential oil. all hydrodistilled-essential oil were tested for antioxidant and antimicrobial activity against pathogens (E. coli). The essential oil has a good activity as antioxidants with IC50 75,77 Âµg/mL. essential oils of kaffir lime leaves were presented antimicrobial activity against E. coli. The essential oil showed weak antimicrobial activity.